Differentiating Carotid Free-Floating Thrombus From Atheromatous Plaque Using Intraluminal Filling Defect Length on CTA: A Validation Study. (24th August 2021) - Torres, Carlos; Lum, Cheemun; Puac-Polanco, Paulo; Stotts, Grant; Shamy, Michel Christopher Frank; Blacquiere, Dylan; Lun, Ronda; Dave, Prasham; Bharatha, Aditya; Menon, Bijoy K.; Thornhill, Rebecca; Momoli, Franco; et al.
Abstract : Objective: To validate a previously proposed filling defect length threshold of >3.8 mm on CT angiography (CTA) to discriminate between free-floating thrombus (FFT) and plaque of atheroma. Methods: This was a prospective multicenter observational study of 100 participants presenting with TIA/stroke symptoms and a carotid intraluminal filling defect on initial CTA. Follow-up CTA was obtained within 1 week and at weeks 2 and 4 if the intraluminal filling defect was unchanged in length. Resolution or decreased length was diagnostic of FFT, whereas its static appearance after 4 weeks was indicative of plaque. Diagnostic accuracy of FFT length was assessed by receiver operating characteristic analysis. Results: Ninety-five participants (mean [SD] age 68 [13] years, 61 men, 83 participants with FFT, 12 participants with a plaque) were evaluated. The >3.8-mm threshold had a sensitivity of 88% (73 of 83) (95% confidence interval [CI] 78%–94%) and specificity of 83% (10 of 12) (95% CI 51%–97%) (area under the curve 0.91, p < 0.001) for the diagnosis of FFT. The optimal length threshold was >3.64 mm with a sensitivity of 89% (74 of 83) (95% CI 80%–95%) and specificity of 83% (10 of 12) (95% CI 51%–97%). Adjusted logistic regression showed that every 1-mm increase in intraluminal filling defect length is associated with an increase in odds of FFT of 4.6 (95% CI 1.9–11.1, p = 0.01). Conclusion: CTA enables accurate differentiation of FFT vs plaque using craniocaudal length thresholds. Trial Registration Information: ClinicalTrials.gov Identifier : NCT02405845. Classification of Evidence: This study provides Class I evidence that in patients with TIA/stroke symptoms, the presence of CTA-identified filling defects of lengths >3.8 mm accurately discriminates FFT from atheromatous plaque.